Insights regarding drug permeation into skin - AL-Mayahy, Mohammed Hussain Neama (2017)
In order to develop safe and effective topical and transdermal formulations to treat either local skin disorders or for systemic drug delivery, it is first imperative to assess skin permeation using a reliable and comprehensive analysis method. The assessment of drug permeation into/across the skin is traditionally accomplished using Franz diffusion cells with subsequent analysis by conventional chromatographic methods such as HPLC and more recently using advanced imaging techniques. In this context, time of flight-secondary ion mass spectrometry (ToF-SIMS) offers distinctive advantages in mapping drugs within skin with high sensitivity and chemical specificity without the need for fluorescent tags or radiolabels. The work in this thesis uses the combination of conventional and advanced methods to evaluate drug permeation into the skin. This approach provides complementary and detailed information regarding the permeated mass, the permeation depth and the spatial distribution and localisation of drugs within skin. As ToF-SIMS does not produce quantitative results, due to the matrix effects, a novel high throughput method was successfully developed to quantify ToF-SIMS data. This method involved the homogenisation of skin tissue followed by microarray printing of this skin homogenate with known concentrations of active pharmaceutical ingredients, specifically imiquimod and chlorhexidine. The subsequent analysis by ToF-SIMS of the resulting array allowed the generation of a calibration curve that can be used in the quantification of the unknown drug concentration in the tape strips. This work has demonstrated the potential of a method to quantify ToF-SIMS data of drugs within skin. Imiquimod is an immune modulator drug approved by the FDA for the treatment of superficial basal cell carcinoma (BCC) but not the nodular lesions. An assessment of imiquimod permeation from commercially available Aldara™ cream into ex vivo porcine skin was carried out using the complementary approach of HPLC and ToF-SIMS analysis. This work represents the most detailed assessment to date of the true extent of permeation of imiquimod from Aldara™ cream as previous studies analysed the permeation of Aldara™ cream showed a limitation in the analytical methodology employed (i.e. analysis by HPLC only). The results showed that imiquimod does permeate into the stratum corneum but is very limited in the deeper skin cell layers. In addition, the ToF-SIMS ion images of Aldara™ cream tape strips illustrated a non-uniform distribution of imiquimod within skin which may result in a decreased efficacy of the cream to uniformly treat whole BCC lesions giving rise to the likelihood of tumour recurrence. This offers previously unobserved insights about the spatial distribution of imiquimod delivered from Aldara™ cream. As other studies have reported that Aldara™ cream has some limitations in the treatment of nodular BCC lesions due to the cream’s inability to deliver imiquimod into the deeper more invasive nodular lesions, an enhancement of imiquimod permeation is thought to be useful to overcome these limitations. Therefore, an attempt to improve delivery of imiquimod into the deeper skin layers using microemulsions and microneedles was investigated. Imiquimod microemulsions were formulated, characterised and then tested for skin permeation enhancement. However, the assessment of imiquimod permeation from the formulated microemulsions alone and with microneedle pre-treatment using HPLC and ToF-SIMS demonstrated a limited ability of the microemulsions to improve delivery of imiquimod over Aldara™ cream. In contrast, Aldara™ cream with microneedle pre-treatment using a derma stamp electric pen showed improved delivery of imiquimod into the skin. This work is believed to be the first attempt to enhance imiquimod delivery using microemulsions and microneedles. Utilising the high sensitivity offered by the ToF-SIMS instrument in the analysis of individual tape strips, an in vivo and ex vivo comparison of chlorhexidine permeation into the stratum corneum was performed using commercial products currently used in hospitals within the UK for skin antisepsis. A comparison was carried out using the tape stripping technique with subsequent analysis of an individual tape strip by ToF-SIMS. The results showed that HiBiSCRUB® 4% produces a higher concentration of chlorhexidine in the upper stratum corneum layers than other products. This work demonstrated the first known application of ToF-SIMS to compare the in vivo skin permeation of commercially available chlorhexidine products and provides the foundation for the potential application of ToF-SIMS in assessing bioequivalence of topical products.